IMPROVING STUDENT LEARNING OUTCOMES THROUGH THE STAD-TYPE ASSISTED EXPERIMENTAL METHOD ON MATERIAL CHANGING THE FORM OF OBJECTS IN CLASS V OF SD NEGERI 1 LAMBHEU - Ramadhan, Wulan Suci; Mislinawati, Mislinawati; Fitriani, Suci (Elementary Education Research, 2025)
Generally, the learning process in schools is still centered on the teacher. Learning activities that are still centered on the teacher cause student activities to be more passive than the teacher, resulting in student learning outcomes that are lower than the predetermined Minimum Completeness Criteria (KKM). To overcome this problem, apply the STAD Type Assisted Experimental Method. The aim of this research is to describe student activities, student responses and to determine student learning outcomes. The approach in this research is a quantitative model with a CAR research type. The research subjects were 28 students. Data collection techniques were observation and tests. The results of data analysis in cycle I obtained a score of 55.82% in the sufficient category. In cycle II the score was 73.71 in the good category and in cycle III the score was 84.90 in the very good category. The learning results in cycle I showed an average score of 50 with a percentage of 25% and cycle II showed a score of 75.71 with a percentage of 53% and cycle III showed a score of 89.28 with a percentage of 88%, so it was determined that this research was sufficient for cycle III only. . Based on the results of student responses to learning outcomes, it was found that 89% of students were very interested in learning using experimental methods. From the data analysis, it can be concluded that the application of the STAD Type Assisted Experimental Method to the Material of Changes in Form of Objects in this research can improve student learning outcomes in class V of SD Negeri 1 Lambheu.